Balance comparison between Iranian elderly with and without knee range of motion limitations - Lohrasbipeydeh, Ehsan; Soh, Kim Geok; Omar Dev, Roxana Dev; Ahrari, Seyedali; Ong, Swee Leong; Siswantoyo; Sunardi, Jaka (Universiti Putra Malaysia, 2021)
This study compares the static eye movement (eyes open and eyes closed) and dynamic balance amongst Iranian elderly with and without knee range of motion (ROM) limitations. The method used was a quasi-experimental before/after study. The participants consisted of 30 older Iranian adults, aged 60 or more (10 females and 20 males across two groups of 15 in each group) who were evaluated using the Sharpened Romberg (SR), Timed Up and Go (TUG) tests. An independent t-test was used to compare the descriptive characteristics of the two groups of the elderly. The findings showed substantial alterations in all the measured components between the subjects. The static balance with an open eye (p = 0.028) and closed eye (p = 0.021), as well as the dynamic balance (p = 0.009) between the elderly with and without the limitation of knee ROM, was substantially different. Moving forward, the findings of this study suggested that the balance of the elderly was directly linked to knee ROM, as the elderly without limitations of knee ROM displayed greater stability than the elderly with limitations of knee ROM. Health care practitioners should also understand the ROM of the knee, as individuals with ROM limitations of the knee are more likely to fall due to underlying disorders associated with their balance.